Oxyresveratrol from mulberry branch extract protects HUVECs against oxidized Low-density Lipoprotein-induced oxidative injury via activation of the Nrf-2/HO-1 pathway. (January 2023) - Shi, Xiaowen; Xu, Li; Zhang, Jianqin; Mo, Juanfen; Zhuang, Pei; Zheng, Li
Graphical abstract: Highlights: Mulberry branch (Morus spp.) is commonly used in traditional Chinese medicine and are also potential functional food additives. Oxyresveratrol was found to be the main anti-oxidant ingredient in the mulberry branch extract that protected HUVECs against ox-ldl -induced injury. Oxyresveratrol could protect HUVECs against the ox-ldl -induced oxidative injury via the dissociation of Nrf-2 from the Keap-1/Nrf-2 to activate the Nrf-2/HO-1 signaling pathway. Oxyresveratrol might be potent in prevention and treatment of atherosclerosis. Abstract: Mulberry branch ( Morus spp.) is an agricultural byproduct enriched with polyphenol and flavone. Mulberry branch extract has been reported to protect human umbilical vein endothelial cells (HUVECs) from oxidized low-density lipoprotein (ox-LDL) injury. However, the active ingredient derived from mulberry branch extract responsible for the protective action and the specific mechanism remain to be clarified. In the current study, the main active ingredient with anti-oxidant activity of mulberry branch extract was rapid-screened using the DPPH-HPLC method. Subsequently, the chemical structure was solved with mass spectrometry and nuclear magnetic resonance spectroscopy. Cell viability, levels of malondialdehyde (MDA) and superoxide dismutases (SODs) were measured to evaluate the protective action of the ingredient for HUVECs against ox-ldl -induced injury. DHE and DCFH-DA fluorescent probes were used to measure the level of intracellular reactive oxygen species (ROS). Real-time qPCR and Western blot were conducted to detect mRNA and protein levels. We found that the Oxyresveratrol was the main anti-oxidant ingredient that protecetd HUVECs against ox-ldl -induced injury. The protective action might be achieved via the up-regulation of the Nrf-2/HO-1 signaling and reduction of ROS production. Futhermore, the protective effect of Oxyresveratrol could be reversed by suppression of Nrf-2. Molecular docking analysis revealed strong binding between Oxyresveratrol and Keap-1/Nrf-2 protein complex, mainly via hydrogen bonds linking the specific amino acid residues on the target proteins. Molecular-dynamics simulation suggested that Oxyresveratrol led to dissociation of Nrf-2 from Keap-1 via binding to the Keap-1/Nrf-2 complex. In all, the current study showed that Oxyresveratrol, an active ingredient of mulberry branch extract, could protect HUVECs against the ox-ldl -induced oxidative injury via the dissociation of Nrf-2 from the Keap-1/Nrf-2 to axtivate the Nrf-2/HO-1 signaling pathway. Thus, the Oxyresveratrol might be potent in prevention and treatment of atherosclerosis.